854. Impact of Antimicrobial Stewardship and Rapid Diagnostics in Children with Staphylococcus aureus Bacteremia - Welch, Stephanie N (Open Forum Infect Dis, 2019)
BACKGROUND: Rapid diagnostic testing (RDT) in combination with antimicrobial stewardship programs (ASPs) has been associated with improved outcomes in adults with Staphylococcus aureus bacteremia (SAB). Data in children are lacking. In January 2017, Atrium Health implemented a pediatric ASP with blood culture RDT. The objective of this study was to determine the impact of those interventions. METHODS: This was a retrospective, multicenter, quasi-experimental study of children ≤18 years with monomicrobial SAB from March 2015 to August 2016 (pre-intervention; PRE) and March 2017 to August 2018 (post-intervention; POST). The primary outcome was time to an optimal antibiotic. Secondary outcomes included time to effective antibiotic, total antibiotic exposure in the first 5 days, duration of bacteremia, infectious diseases (ID) consultation, time to central line removal, hospital and pediatric ICU length of stay (LOS), need for vasopressors or intubation, recurrence of SAB within 90 days, and inpatient mortality. RESULTS: Of 101 patients with SAB, 32 and 36 met inclusion criteria for the PRE and POST groups, respectively. The median time to optimal antimicrobial therapy decreased by 23 hours (PRE 44.3 hours vs. POST 21.3 hours; P = 0.008). Duration of bacteremia (65h vs. 40.9 hours; P = 0.028) and mortality (12.5% vs. 0%; P = 0.044) was also significantly reduced. Differences in median time to effective therapy (7 hours vs. 5.1 hours; P = 0.74), total antibiotic exposure in the first 5 days (160.4 hours vs. 152 hours; P = 0.4), hospital LOS (9.9 vs. 8.5 days; P = 0.25), and pediatric ICU LOS (7 vs. 4 days; P = 0.11) did not meet statistical significance, but trended downward. The POST group had more patients with ID consultation (78% vs. 89%, P = 0.23) and shorter time to central line removal (68 hours vs. 20 hours; P = 0.037). There was no difference in the need for vasopressors (3 vs. 3 patients; P = 0.99) or intubation (2 vs. 4 patients; P = 0.68). Throughout the study period, recurrence of SAB only occurred in one patient (PRE). CONCLUSION: Concurrent implementation of RDT and an ASP in pediatric patients with SAB decreased time to optimal antimicrobial therapy, duration of bacteremia, and mortality. RDT coupled with timely feedback from an ASP contributed to improved SAB management and clinical outcomes in children. DISCLOSURES: All Authors: No reported Disclosures.